Technical-economic analysis of a family farm: Case study ; Gheraseni Parish, Buzau Country - Petruţa Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
In Romania, family farms strenghten agriculture stability wise through structural changes in multifunctional development, merchandising of vegetable products, making investments and depositing products. The family farms production structure was formed under factors like: natural environmet, market, financial capital, the risk and uncertainty related to selling products, conumption. At the same time it's considered to be the central element of the agricultural structures and it's regarded in independence with the elements that contribute in obtaining agricultural products.
Keywords: 330; production structure; agricultural production; work productivity